NLRP3 Inflammasome as a Molecular Marker in Diabetic Cardiomyopathy - Luo, Beibei; Huang, Feng; Liu, Yanli; Liang, Yiying; Wei, Zhe; Ke, Honghong; Zeng, Zhiyu; Huang, Weiqiang; He, Yan (Frontiers in Physiology, 2017)
Diabetic cardiomyopathy (DCM), a common consequence of longstanding diabetes mellitus, is initiated by death of cardiomyocyte. Hyperglycemia-induced reactive oxygen species (ROS) overproduction is a major contributor of the chronic low-grade inflammation that characterizes as the DCM. ROS may promote the activation of nucleotide-binding oligomerization domain like receptor (NLR) pyrin domain containing 3 (NLRP3) inflammasome, a novel regulator of inflammation and cell death, by nuclear factor-kB (NF-kB) and thioredoxin interacting/inhibiting protein (TXNIP). NLRP3 inflammasome regulates the death of cardiomyocyte and activation of fibroblast in DCM, which is involved in the structural and functional disorder of DCM. However, comprehensive understanding of molecular mechanisms linking NLRP3 inflammasome and disorder of cardiomyocyte and fibroblast in DCM is lacking. Here we review the molecular mechanism(s) of NLRP3 inflammasome activation in response to hyperglycemia in DCM.